Design and fabrication of tennis ball picker / Muhamad Adib Hakimie Mohd Arifin - Mohd Arifin, Muhamad Adib Hakimie (2022)
These days, most of the people spend a lot of time in training session and it is include the time for cleaning the court. It is because the amount of balls that have beenused for the entire training session. In addition, the probability for people from suffer from back pain is increase without the use of this product. The goal of this project is to target sports shops that sell sports equipment, sports schools, or sports clubs. The group needs this product to make it easier for tennis players to use it while practicing or playing casually. To produce new alternatives of non -electric tennis ball pickers forprofessional athletes, coaches, and ball pickers. It can help them save time and energythrough low-cost design and development.